Scalable and durable module-sized artificial leaf with a solar-to-hydrogen efficiency over 10% - Dharmesh Hansora; Rashmi Mehrotra; Eunseo Noh; Jin Wook Yoo; Minkyung Kim; Woo Jin Byun; Jaewang Park; Ji-Wook Jang; Sang Il Seok; Jae Sung Lee (Nature Communications)
Abstract An artificial leaf mimicking the function of a natural leaf has recently attracted significant attention due to its minimal space requirement and low cost compared to wired photoelectrochemical and photovoltaic-electrochemical systems for solar hydrogen production. However, it remains a challenge to achieve a practical-size solar water-splitting device that can fulfill the criteria of a solar-to-hydrogen conversion efficiency above 10%, long-term durability, and scalability. Here, we develop 1 cm2 perovskite-based photoelectrodes using a defect-less, chlorine-doped formamidinium lead triiodide as photo-absorber and ultraviolet-insensitive tin oxide as an electron transport layers. This device is encapsulated using electrocatalyst-deposited nickel foils, which demonstrates high photocurrent density and high stability for 140 h. Ultimately, we fabricate a scalable mini-module-sized artificial leaf (16 cm2) consisting of a side-by-side/parallel configuration of photoanode and photocathode architecture integrated with a 4 × 4 array of 1 cm2 photoelectrodes, which maintains a stable ‘module-level’ solar-to-hydrogen efficiency of 11.2% in an unbiased solar water-splitting under 1-sun illumination.